(untitled) (Jurnal Ilmu Gizi dan Dietetik, 2022)
The provision of emergency food is crucial in areas with high-risk disasters. This food can be made from local commodities such as mung bean and black rice. This study aimed to obtain the best formulation of ready-to-eat porridge from mung bean and black rice, which can be an emergency food. The study was conducted from April to June 2021. The treatment formulation consisted of three formulas with a ratio of mung bean to black rice: F1 (60:40), F2 (70:30), and F3 (80:20). The results showed that the selected formula was F1 with a ratio of 60% mung bean and 40% black rice. Analysis of the nutritional content per serving (300 g) contains 535 kcal of energy, 20.6 g of protein, 9.2 g of fat, 92.6 g of carbohydrates, and 21.8 g of dietary fiber. The nutritional content of F1 can fulfill 24.9% for general consumers based on ALG and is claimed to be high in fiber. The shelf-life of the porridge (25°C) is 21 days.